Development of GEM trigger electronics for the J-PARC E16 experiment. Issue 8 (December 2015) - Obara, Y.; Hamada, E.; Ikeno, M.; Kawama, D.; Morino, Y.; Nakai, W.; Ozawa, K.; Sendai, H.; Takahashi, T. N.; Tanaka, M. M.; Uchida, T.; Yokkaichi, S.
Abstract: At the J-PARC E16 experiment[1], we measure mass spectra of vector mesons in nuclei from the e+e - decay channel with high precision and high statistics. We have developed the trigger system consisting of newly developed ASD ASICs which can extract signals from the GEM foil used as a cathode plane of the induction gap in a GEM chamber and digital electronics using FPGAs which processes binary signals from the ASIC.